Probing the Phylogenomics and Putative Pathogenicity Genes of Pythium insidiosum by Oomycete Genome Analyses - Rujirawat, Thidarat (Sci Rep, 2018)
Pythium insidiosum is a human-pathogenic oomycete. Many patients infected with it lose organs or die. Toward the goal of developing improved treatment options, we want to understand how Py. insidiosum has evolved to become a successful human pathogen. Our approach here involved the use of comparative genomic and other analyses to identify genes with possible functions in the pathogenicity of Py. insidiosum. We generated an Oomycete Gene Table and used it to explore the genome contents and phylogenomic relationships of Py. insidiosum and 19 other oomycetes. Initial sequence analyses showed that Py. insidiosum is closely related to Pythium species that are not pathogenic to humans. Our analyses also indicated that the organism harbours secreted and adhesin-like proteins, which are absent from related species. Putative virulence proteins were identified by comparison to a set of known virulence genes. Among them is the urease Ure1, which is absent from humans and thus a potential diagnostic and therapeutic target. We used mass spectrometric data to successfully validate the expression of 30% of 14,962 predicted proteins and identify 15 body temperature (37 °C)-dependent proteins of Py. insidiosum. This work begins to unravel the determinants of pathogenicity of Py. insidiosum.